LEGAL PROTECTION FOR ODONG-ODONG TRANSPORTATION USERS UNDER LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Miftahuddin, Miftahuddin; Musthofa, Ahmad Misbakh Zainul; Anggi Irawan (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Odong-odong transportation is a form of entertainment widely used by the public, especially in tourist areas. However, in practice, odong-odong operations often do not meet the standards of eligibility and legal permits according to applicable laws. This can potentially endanger users of transportation services, resulting in material and immaterial losses. This study aims to analyze the form of legal protection for consumers and the responsibilities of business actors in providing consumer security and safety guarantees based on Law Number 8 of 1999 concerning Consumer Protection. The research method used is juridical-empirical by implementing normative legal provisions to events that occur in society, and supported by interview results as primary data and related literature as secondary data. The results of the study indicate the importance of fulfilling the rights of odong-odong transportation users. Therefore, in addition to enforcing laws and regulations, the government needs to play a role in supervising so that legal protection for consumers becomes more optimal. Keywords: Consumer Protection, positive law, odong-odong